Transforming the Insurance Industry with Salesforce: Enhancing Customer Engagement and Operational Efficiency - Gayathri Mantha (North American Journal of Engineering Research, 2024)
The insurance industry is experiencing noteworthy change driven by mechanical progressions. This white paper investigates how Salesforce can be utilized to progress client engagement, streamline operations, and upgrade by and large benefit conveyance within the insurance sector.